A validation study of a clinical prediction rule for screening asymptomatic chlamydia and gonorrhoea infections among heterosexuals in British Columbia. (30th April 2015) - Falasinnu, Titilola; Gilbert, Mark; Gustafson, Paul; Shoveller, Jean
Abstract : Background: One component of effective sexually transmitted infections (STIs) control is ensuring those at highest risk of STIs have access to clinical services because terminating transmission in this group will prevent most future cases. Here, we describe the results of a validation study of a clinical prediction rule for identifying individuals at increased risk for chlamydia and gonorrhoea infection derived in Vancouver, British Columbia (BC), against a population of asymptomatic patients attending sexual health clinics in other geographical settings in BC. Methods: We examined electronic records (2000–2012) from clinic visits at seven sexual health clinics in geographical locations outside Vancouver. The model's calibration and discrimination were examined by the area under the receiver operating characteristic curve (AUC) and the Hosmer–Lemeshow (H-L) statistic, respectively. We also examined the sensitivity and proportion of patients that would need to be screened at different cut-offs of the risk score. Results: The prevalence of infection was 5.3% (n=10 425) in the geographical validation population. The prediction rule showed good performance in this population (AUC, 0.69; H-L p=0.26). Possible risk scores ranged from −2 to 27. We identified a risk score cut-off point of ≥8 that detected cases with a sensitivity of 86% by screening 63% of the geographical validation population. Conclusions: The prediction rule showed good generalisability in STI clinics outside of Vancouver with improved discriminative performance compared with temporal validation. The prediction rule has the potential for augmenting triaging services in STI clinics and enhancing targeted testing in population-based screening programmes.